Education for sustainable development in physical education: Program development by use of intervention mapping - Bucht, Charlotta; Mess, Filip; Bachner, Joachim; Spengler, Sarah (Frontiers in Education, 2022)
There is little information on the development of school-based programs to change students’ sustainability behavior. The goal of this article is to describe the systematic development and the content of a program that includes education for sustainable development in regular physical education. The Intervention Mapping approach was used as a methodological framework for program design. Participatory workshops with relevant stakeholders and experts were part of the process. Considering the physical education curriculum with its multiple objectives, four main behavioral outcomes were derived: Reduction in clothes consumption, change in diet, change in dealing with trash and increased usage of bike/public transportation. Behavior change methods were specifically selected to be suitable for physical education. The developed practical applications are in line with the physical education curriculum. It is reflected on the use of intervention mapping as a methodological framework for program design in the specific field of sustainability behavior and the equally specific setting of physical education. Benefits and limitations of the developed program are discussed.